2017
DOI: 10.1111/pde.13216
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis Suppurativa in Children Treated with Finasteride—A Case Series

Abstract: Treatment of HS can be challenging. The options available include antimicrobials, immunosuppressants, hormonal therapies, lasers, and surgery. The authors report the largest series of children with HS treated with finasteride. The results support the use of finasteride as monotherapy for the treatment of this disease in children. Further studies are necessary to fully understand the role of this drug in the management of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 12 publications
(27 reference statements)
0
29
0
Order By: Relevance
“…Although patients with HS do not seem to have increased levels of androgens, beneficial clinical responses have been reported with antiandrogens, such as cyproterone acetate, spironolactone and the 5α‐reductase inhibitor finasteride . Peroxisome proliferator‐activated receptor‐γ (PPARγ) regulates adaptive immunity through Th17 differentiation and Treg functions .…”
Section: Therapeutic Agents Affect the T Helper 17 Cell/regulatory T‐mentioning
confidence: 99%
“…Although patients with HS do not seem to have increased levels of androgens, beneficial clinical responses have been reported with antiandrogens, such as cyproterone acetate, spironolactone and the 5α‐reductase inhibitor finasteride . Peroxisome proliferator‐activated receptor‐γ (PPARγ) regulates adaptive immunity through Th17 differentiation and Treg functions .…”
Section: Therapeutic Agents Affect the T Helper 17 Cell/regulatory T‐mentioning
confidence: 99%
“…A report showed no new HS lesions 3 months following finasteride treatment, while another showed faster healing lesions (3 weeks vs. 6 months) and ultimately no new lesions after 3 years . Case series of girls with HS (6–11 years old) treated with finasteride (1–5 mg/day) for 24 months had overall improvement of disease, with a reduction in frequency and intensity of flares …”
Section: Resultsmentioning
confidence: 96%
“…A couple case series examined finasteride (5 mg/day) for hidradenitis suppurativa (HS) therapy . Five women and two men with HS unresponsive to antibiotics were treated with finasteride.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Randhawa et al 109 used finasteride as adjunctive therapy with significant improvement in a 7 years-old child and two 15 years-old adolescents, all female, 2 of them with concomitant endocrine disorders. Recently, Mota et al, 110 reported five cases of children with HS Hurley I (4 girls and 1 boy, diagnosed between the ages of 6 and 11 years) treated with oral finasteride as monotherapy (increasing dose up to 5 mg/day) with overall improvement and no adverse effects, but 2 patients relapsed after stopping treatment.…”
Section: -Antiandrogenic Therapymentioning
confidence: 99%